Emotion regulation difficulties and cognitive emotional regulation in patients with temporal lobe epilepsy - Masjedi Arani, Abbas; Batebi, Sepideh; Dolatshahi, Behrooz; Azimian, Mojtaba (Researcher Bulletin of Medical Sciences, 2022)
Objective: Temporal lobe epilepsy (TLE) is one of the most prevalent types of complex partial epilepsy in adults. Due to the damage to the amygdala, patients with TLE struggle with emotional problems. The purpose of this study was to investigate the functions of emotion regulation and cognitive-emotional self-regulation in patients with TLE compared to non-epileptic individuals. Method: In this study, 80 patients with TLE were recruited based on some inclusion criteria and compared with 80 non-epileptics by considering their emotional functions. Questionnaires for evaluating difficulties in emotion regulation (Gratz & Roemer) and cognitive emotional regulation (Garnefski) were given to the participants of the study. Finally, data analysis was performed using multivariate analysis of variance (MANOVA) by SPSS 19 Statistics. Results: The results of MANOVA test showed a significant difference between the components of difficulties in emotion regulation as well as cognitive-emotional regulation between patients with TLE and the healthy group (P<0.01). Conclusion: Patients with TLE had more difficulties in emotion regulation and higher negative cognitive emotional regulation strategies than healthy subjects.